After the fire: Perceptions of land use planning to reduce wildfire risk in eight communities across the United States - Mockrin, Miranda H.; Fishler, Hillary K.; Stewart, Susan I. (International journal of disaster risk reduction, 2020)
Wildfire losses are increasing across the United States, and yet land use planning to reduce wildfire risk is not federally mandated and is rarely used by local jurisdictions. We examined local government staff and leaders’ perceptions of land use planning and regulations to reduce wildfire risk, in a range of communities, after wildfire risk had been made evident with the loss of homes due to wildfire. Although policy after fire was largely unchanged we found local leaders had devoted substantial attention to the subject of land use planning. Communities were dealing with a number of internal concerns, including staff perceptions of wildfire risk, staff opinions of planning and regulations, policy coordination challenges, other governmental priorities, and a lack of public support for land use planning and regulations to reduce wildfire risk. Many of these considerations were present across study sites, and thus not easily linked to characteristics of the study site (rural/urban, type of housing lost to wildfire, presence of amenity growth). The scale and scope of local government, the diversity of residents and development, and the social fit between policies and local settings all combine to determine the efficacy and use of land use planning and regulations to reduce wildfire risk. Wildfire is unique among hazards in that the threat continues to evolve along with development, requiring local communities to adapt strategies over time. Successful examples of using land use planning and regulations, in a range of settings, will be increasingly valuable in disseminating the concept of fire adapted communities.